Chronicle of a death foretold : a novel - García Márquez, Gabriel, 1927-2014 (Vintage International, 2003)
Angela Vicario's husband returns his new bride to her family hours after the marriage, claiming she is a dishonored woman. Angela's family forces her to reveal her first lover's name, and her twin brothers set out to murder the man, Santiago Nasar. As the murder is planned, no one in the town tries to stop the crime, which results in an entire society put on trial for the murder.